2023
DOI: 10.53889/ijses.v3i1.132
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Cybersecurity Challenges in Education

Abstract: This study aimed to address the challenges of cybersecurity in education. As kindergarten through twelfth-grade education shifts to online and remote learning, educators and governments are increasingly vulnerable to the risks of cyberattacks and cybercrimes. This study focused on the strategies that institutions can employ to increase their students’ cybersecurity awareness and simultaneously motivate them to pursue cybersecurity as a career. To achieve the research objectives, a systematic review of ten stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…COVID-19 induced a transition to online learning which has made cybersecurity for students an interesting research area. Triplett [31] carried out a review study to find out how children's cybersecurity awareness was important, and concluded that the adoption of game-based strategies to increase children's awareness could be effective. Zorlu [32] conducted an empirical study with students of Bartin University, Turkey, and found that college students required awareness to keep themselves protected against cyberbullying and cybersecurity threats.…”
Section: Cybersecurity and Online Learningmentioning
confidence: 99%
“…COVID-19 induced a transition to online learning which has made cybersecurity for students an interesting research area. Triplett [31] carried out a review study to find out how children's cybersecurity awareness was important, and concluded that the adoption of game-based strategies to increase children's awareness could be effective. Zorlu [32] conducted an empirical study with students of Bartin University, Turkey, and found that college students required awareness to keep themselves protected against cyberbullying and cybersecurity threats.…”
Section: Cybersecurity and Online Learningmentioning
confidence: 99%
“…Cybersecurity, including pentesting, is a complex subject matter, thus, the learners' motivation is very important to ensure success in cybersecurity learning, especially as learners may experience some difficulties to grasp the intricate concepts of cybersecurity (Kam et al, 2020). Game-based strategies are considered effective in increasing students' cybersecurity awareness and their decision to become cybersecurity professionals (Triplett, 2023). Specifically for the new talent attraction, cyber competitions or exercises (such as Capture the Flags (CTFs)) organized by universities or non-profit organizations are considered as effective ways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the competitions positively influence future career intents, they are designed for targeting high schoolers and those undecided undergraduate and graduate students (Bashir et al, 2015). Recently, both high school and college level students have become increasingly interested in studying cybersecurity; therefore, educational institutions also design introductory courses and seminars to expand the students' knowledge of cybersecurity (Triplett, 2023). However, graduates, non-cybersecurity majors, or those already established in the career path with certain intentions, attracting them to competitions or traditional cybersecurity awareness courses may not work, and alternatives should be considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…10.52889/citj.v1i1.296 AI role in STEM education is more comprehensive and detailed. Instead of broadly considering AI educational implications, we have focused specifically on STEM-specific contexts.Furthermore, educators have discovered that students in high school and college have become increasingly interested in studying; thus, in addition to introductory courses, they have designed seminars to expand he students' knowledge findings complement those ofTriplett (2023), which had previously suggested the immense potential of STEM education without delving into the specific implementation challenges. The implications of the findings from this study are manifold.…”
mentioning
confidence: 99%